Translanguaging Pedagogy for Meaning Making through Classroom Interactional Competence in Thai EMI Context - Nooyod, Aummaraporn; A. Ambele, Eric (NIDA Journal of Language and Communication, 2025)
Translanguaging can be conceptualized as a theory of communication and language use, and, involves the fluid use of multiple languages as an integrated system of communication. It is the process where individuals employ their full linguistic and semiotic capabilities to make meaning, considering languages not as fixed codes by themselves, but as fluid codes framed within social practices. Pedagogical translanguaging is a practice that refers to instructional strategies integrating two or more languages in naturally occurring contexts where boundaries between languages are fluid and constantly shifting. It provides spaces to encourage learners’ understanding through discussion activities by using different languages for input and output. This paper explores how translanguaging contribute to knowledge construction of interaction competence within the Thai English Medium Instruction classroom. In particular, the classroom interaction competence builds on ideas related to the centrality of interaction in language learning and focuses on the ways in which teachers’ and learners’ interactional decisions create learning opportunities in the classroom. Employing translanguaging through classroom interactional competence can encourage learners’ deployment of different semiotic resources, especially their free choice and use of languages, in the process of dialogic knowledge construction. The learners can utilize their full linguistic and multimodal repertoires to construct knowledge and facilitate meaning-making processes in the classroom. Therefore, translanguaging can give learners deeper insight into the subject matter discussed and has the potential to promote higher-order thinking and fuller understanding.